2018
DOI: 10.1371/journal.pone.0195974
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of basic helix-loop-helix superfamily members in peach

Abstract: The basic helix-loop-helix (bHLH) transcription factor family is a superfamily found in all eukaryotes that plays important roles in regulating growth and development. Over the past several decades, many bHLH superfamily genes have been identified and characterized in herbaceous and woody plants. However, the genes belonging to the bHLH superfamily in peach (Prunus persica) have not yet been comprehensively identified and characterized. Here, we identified 95 members of the bHLH superfamily in the peach genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 48 publications
8
52
0
Order By: Relevance
“…In addition, among the 73 CpbHLHs, one protein (CpbHLH003) exhibited incomplete bHLH domains, whereas the remaining 72 bHLH proteins all presented complete bHLH domains. Similar observations have been made in other plant species, such as peach and blueberry [22,36].…”
Section: Phylogenetic Analysis Gene Structure Conserved Motifs Analsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, among the 73 CpbHLHs, one protein (CpbHLH003) exhibited incomplete bHLH domains, whereas the remaining 72 bHLH proteins all presented complete bHLH domains. Similar observations have been made in other plant species, such as peach and blueberry [22,36].…”
Section: Phylogenetic Analysis Gene Structure Conserved Motifs Analsupporting
confidence: 87%
“…Transcription factors (TFs) play key roles in the stress regulation network and signal pathways in plants. Basic/helix-loop-helix (bHLH) TFs are the second largest TFs family in plants and have been identified in many species [6,[18][19][20][21][22][23][24][25]. However, the bHLH TF family has not previously been reported in papaya (Carica papaya L.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported genome-wide identi cation and classi cation of bHLH factors in plants [18,19,28,29,30]. Although the genomes of Arabidopsis thaliana and Oryza sativa possess four and six subclade IVa members, respectively [19], more than 30 subclade IVa bHLH genes were found in the genomes of Glycine max and M. truncatula [21,28].…”
Section: Introductionmentioning
confidence: 99%